Reverse shape selectivity in the liquid-phase adsorption of xylene isomers in zirconium terephthalate MOF UiO-66 - Mariana A. Moreira (2012)
Powder, agglomerates, and tablets of the microporous zirconium(IV) terephthalate metalorganic framework UiO-66 were evaluated for the selective adsorption and separation of xylene isomers in the liquid phase using n-heptane as the eluent. Pulse experiments, performed at 313 K in the presence of n-heptane, revealed the o-xylene preference of this material, which was further confirmed by binary and multicomponent breakthrough experiments in the presence of m- and p-xylene, resulting in selectivities at 313 K of 1.8 and 2.4 with regards to m-xylene and p-xylene, respectively. Additionally, because p-xylene is the less retained isomer, UiO-66 presents a selectivity pattern that is reverse of that of the xylenes' molecular dimension with respect to shape selectivity. The shaping of the material as tablets did not significantly change its selectivity toward the o-xylene isomer or toward p-xylene, which was the less retained isomer, despite a loss in capacity. Finally, the selectivity behavior of UiO-66 in the liquid n-heptane phase makes it a suitable material for o-xylene separation in the extract (heavy product) or p-xylene separation in the raffinate (light product) by simulated moving bed technology.